Thermal transport in twinning superlattice and mixed-phase GaAs nanowires. Issue 17 (13th April 2022) - Ghukasyan, Ara; LaPierre, Ray
Abstract : The thermal conductivity of twinning GaAs nanowires varies non-monotonically with the twin period. A minimum thermal conductivity is obtained when the twin period is approximately 50 Å, regardless of nanowire diameter. Abstract : With continuing advances in semiconductor nanowire (NW) growth technologies, synthesis of tailored crystal structures is gradually becoming a reality. Mixtures of the bulk zinc blende (ZB) and wurtzite (WZ) phase can be achieved in III–V NWs under various growth conditions. Among the possible crystal structures, the twinning superlattice (TSL) has attracted particular interest for tuning photonic and electronic properties. In this work, we investigated the mechanisms underlying thermal transport in pristine, TSL, and disordered polytypic GaAs NWs, using non-equilibrium molecular dynamics and transmission spectra obtained from the atomistic Green's function method. We found that a TSL period of 50 Å minimizes the thermal conductivity and determine a phonon coherence length of about 20 to 50 nm, depending on the NW diameter. Our findings indicate strong dependence of the thermal conductivity on the NW surface and internal structure at a given diameter, critical for thermoelectric optimization.